How does capital structure affect firm's market competitiveness? (Cấu trúc vốn ảnh hưởng như thế nào đến khả năng cạnh tranh trên thị trường của doanh nghiệp?) - Nga Thi Viet Nguyen; Chi Thi Kim Nguyen; Phuong Thi Minh Ho; Huong Thi Nguyen; Duy Van Nguyen (My University, 2021)
How does capital structure affect firm's market competitiveness? (Cấu trúc vốn ảnh hưởng như thế nào đến khả năng cạnh tranh trên thị trường của doanh nghiệp?)
Keywords: Capital structure; Market competitiveness; Corporate finance; Firm performance